Hubungan Pola Konsumsi Dengan Gizi Lebih Dan Obesitas Di Kota Jayapura - Natalia Paskawati Adimuntja; Fajrin Violita; Asriati Asriati; Lisda Oktavia Madu Pamangin; Christin Debora Nabuasa (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2026)
Overweight and obesity are risk factors for many chronic diseases, such as diabetes mellitus and cardiovascular disease, including heart disease and stroke, which are among the main causes of death worldwide. The prevalence of overweight in adults aged 18 years and over in Papua in 2023 was 14,2%. Meanwhile, the prevalence of obesity in Papua in 2023 was 31,3%. This study aims to determine the relationship between dietary habits and overnutrition and obesity in Jayapura city. This study used a cross sectional survey design. The population was all adult patients who visited the Abepura Community Health Center in Jayapura City, with a sample size of 100 respondents. The sampling technique used was accidental sampling. Data were collected through interviews using a questionnaire. The data were analyzed using univariate analysis and bivariate analysis with the chi-square (χ²) statistical test. The results of the study showed that 44 respondents (44,0%) experienced overnutrition and obesity and 56 respondents (56,0%) were not obese. The results of the bivariate analysis found that fast food consumption habits (p-value=0,000), soft drink consumption habits (p-value=0,004), fruit consumption habits (p-value=0,05), and vegetable consumption habits (p-value=0,044) were significantly associated with overweight and obesity among adults at the Abepura Community Health Center in Jayapura City. It is recommended that the community increase their understanding and awareness of the importance of maintaining ideal body weight through a high-fiber diet and avoiding fast food and soft drinks as an effort to prevent and control degenerative diseases.